Appalachian Curriculum 1998 - Pillis, Carolyn (Appalachian State University, 1998)
An Appalachian Curriculum is the product of a week-long symposium workshop held at Radford University In June 1998. The purpose of the workshop was to create materials that allowed children from the Southern Appalachian region to gain better access to the natural and cultural resources available on the Blue Ridge Parkway.